EFFECT OF CAPTIAL STRUCTURE ON FINANCIAL PERFORMANCE OF MANUFACTURING COMPANIES IN NIGERIA - JOSIAH, Faith Onyinyechi; UGURU, Leonard C; NKWAGA, Louis C. (EBSU Journal of Social Sciences and Humanities, 2024)
This study examined the effect of capital structure on financial performance of manufacturing companies in Nigerian exchange group (NXG). Ex post facto research design was used with a sets of data for of 10 years spanning from 2011–2021 as gathered from the annual reports and account of the ten (10) sampled companies. The study employed cross sectional panel multiple regressions. It was anchored on the stakeholder theory. The result revealed that equity capital financing has a negative relationship and insignificant effect on return on assets of listed manufacturing firms in Nigeria. This can be observed from the value of beta coefficient of (-0.046194) with p-value of 0.8934 indicating that the p-value is not statistically significant at 5%. Monetary policy interest rate and total debt capital financing also has a negative relationship and insignificant effect on return on assets. This can be seen from the beta coefficient of (-3.895932) and (-3.857009) respectively and p-value of 0.5319 and 0.3054 respectively indicating that the p-value is not statistically significant at 5%. The implication of the findings is that many companies in Nigeria are into window dressing of accounts which is not favourable to fund providers in the Nigerian manufacturing firms. It is therefore recommended among others that companies should look critically and make comparison between the cost of obtaining a particular source of capital and the benefit that can be derived from it instead of making capital structure decisions on baseless generalizations. This will help managers ensure that there will be a gain at the end of the day.